Implementation of Angklung Beat Density With Arduino and Piezoelectric Sensor Using Kalman Filter Applied for Reduce Noise Sensor - Imron; Bagus Satria; Mika Debora Br Barus (CERED Indonesia Institute, 2022)
Angklung is a musical instrument consisting of several bamboo pipes arranged vertically and tied with string or rattan, so that when it is hit or shaken it produces a different sound depending on the size and thickness of the bamboo pipe. The vibrations given will cause the resulting sound resonance. The position of the handrails and how to shake are good learning parameters for beginners in operating the angklung. Knowing the number of vibrations or beats on the angklung can provide harmonization and resonance to be played together. These conditions require measurement and observation methods with the beat density of the angklung to form synchronization and harmonization. Piezoelectric sensors and Arduino are used to read the resulting vibrations. Under the conditions of the resulting vibration will cause noise. In the process of removing noise or interference, it is carried out using the Kalman Filter algorithm. The Kalman Filter algorithm is one that is widely used for noise filtering and for estimating the state of the system. The average obtained for knocks without using Kalman Filter is 9.3 beats and for those using Kalman Filter is 7.8 for a target of 5 beats. While the results of the 20-beat target condition produce an average for sensors without Kalman Filter producing an average number of beats of 25.3 and those using Kalaman Filter produce an average value of 23.3 beats.